Investigating AI Chatbots’ Role in Online Learning and Digital Agency Development - Irina Engeness; Magnus Nohr; Trine Fossland (Education Sciences, 2025)
The integration of artificial intelligence (AI) chatbots in online learning environments has transformed the way students engage with educational content, offering personalised learning experiences, instant feedback, and scalable support. This study investigates the role of AI-driven chatbots in the Pedagogical Information and Communication Technology (ICTPED) Massive Open Online Course (MOOC), a professional development course aimed at enhancing teachers’ Professional Digital Competence (PDC). The study pursues two connected aims: (1) to examine how chatbots support content comprehension, self-regulated learning, and engagement among pre- and in-service teachers, and (2) to explore, through a cultural-historical perspective, how chatbot use contributes to the development of students’ digital agency. Based on data from 46 students, collected through structured questionnaires and follow-up interviews, the findings show that chatbots functioned as interactive learning partners, helping students clarify complex concepts, generate learning resources, and engage in reflection—thereby supporting their PDC. At the same time, chatbot interactions mediated learners’ development of digital agency, enabling them to critically interact with digital tools and navigate online learning environments effectively. However, challenges such as over-reliance on AI-generated responses, inclusivity issues, and concerns regarding content accuracy were also identified. The results underscore the need for improved chatbot design, pedagogical scaffolding, and ethical considerations in AI-assisted learning. Future research should explore the long-term impact of chatbots on students’ learning and the implications of AI-driven tools for digital agency development in online education.